Evaluation Method for Vibration Measurement on Casing in Aeroengine: Theoretical Analysis and Experimental Study - Lanlan Hou; Shuqian Cao (Shock and Vibration)
The vibration measurement location is the basis for effective monitoring of aeroengine vibration conditions. Measurement locations need to reflect the vibration of the rotor sufficiently, while complex structures of the aeroengine bring many excitation sources. This paper presents an evaluation methodology for vibration measurement on casing in the aeroengine. A number of indexes are defined to quantify and characterize the vibration measurement ability of main measurement locations on casing for rotor vibration. A dynamic model of a dual-rotor-casing system is established according to the support structure of a certain type of aeroengine. By means of the introduced evaluation method, the vibration relation between rotors and the main vibration measurement sections is analyzed. Response characteristics and performance orders of measurement sections are given. The rationality of theoretical results is sound verified by experiments on a designed pneumatic-driven double-rotor-casing test bench. The best measured vibration section is consistent with the actual on-board vibration section of the engine, which further demonstrates the effectiveness of the evaluation method. The research results can provide a basis for the selection and optimization of vibration measurement locations and fault diagnosis in the aeroengine. Furthermore, the application of this method is not limited to aeroengine vibration analysis and sensor measurement location optimization, but will be useful for vibration analysis of other rotating machinery.